Analysis of factors that influence students' lack of reading ability in Indonesian language subjects in elementary schools - Mertadi, Mertadi; Fitriana, Maulida Arum; Junaidi, Junaidi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to describe the analytical factors that influence the lack of reading ability of lower grade students in Indonesian language subjects. This research was carried out at SDN I Senaru, Batukoq Hamlet, Senaru Village, Bayan District, North Lombok Regency. The object of research is the factors that cause the lack of reading ability of lower grade students in Class II Elementary School where their age ranges from 7-8 years, namely the transition period after toddlerhood to childhood. The age in this research is what causes the low reading ability in class II. The research method used is qualitative research because the data obtained in the field is more in the form of information and information about the conditions of students as they are in the field using observation, interviews and documentation methods, then looking at the results of the analysis of factors that influence the lack of reading ability of low grade students so that It can be concluded that the lack of reading ability is caused by four factors, namely 1). Physiological Factors, 2). Intelligence Factor, 3). Environmental factors and 4), Psychological factors. Some of these factors cause learning outcomes and learning achievements to be not as effective as other friends who are already fluent in reading and this becomes an obstacle for teachers and others.